An Atom-Economical Approach to the Synthesis of Potentially Bioactive 2H-Chromenes via CuI-Catalyzed Reactions of Alkyl/Aryl-(E)-(o-Propargyloxy)styryl Ketones - Majumdar, K. C.; Ansary, Inul; Shyam, Pranab K.; Roy, B. (Synlett, 2012)
A series of potentially bioactive 2H-chromenes have been synthesized in good yields (60–82%) via CuI-catalyzed reactions of alkyl/aryl-(E)-(o-propargyloxy)styryl ketones in an atom-economical approach.
Keywords: aldol condensation; alkyl/aryl-(E)-(o-propargyloxy)styryl ketones; copper(I) iodide; 2H-chromenes; atom economy